Effects of territory size on the reproductive success and social system of the giant otter, south‐eastern Peru. (21st April 2015) - Groenendijk, J.; Hajek, F.; Schenck, C.; Staib, E.; Johnson, P. J.; Macdonald, D. W.
Abstract The link between resource abundance, dispersion and cooperative breeding in mammals has been a topic of much debate among ecologists. The giant otter social system is facultatively cooperative. Extended families inhabit home ranges where only a dominant pair breeds, and other family members assist with cub defence and food provision. But this system can be affected by local ecology. In the floodplain of the Manu River, in Manu National Park, Peru, oxbow lakes are patchily distributed and form the resource‐rich cores, or territories, of giant otter family home ranges. We present data from a long‐term study at this site, linking territory size variability to the composition of resident giant otter groups and their reproductive success. Territory size predicts group structure; both the size of groups and the number of post‐emergence cubs are positively correlated to the total lake area within the group territory. Territories with small lake areas (likely to be poor territories) often support only a pair, and the pair may not breed successfully every year. Cubs are more likely to survive in years when more non‐breeding adults are present at the time of emergence. However, there may be a negative effect on survival where more non‐breeding adults are present in the subsequent year. Finally, cubs produced in larger territories are more likely to disperse and breed successfully away from the natal territory. We conclude that giant otter societies are likely shaped by the spatial dispersion of lakes, and food abundance and dispersion within these rich patches.